Caught Between Autonomy and Insecurity: A Work-Psychological View on Resources and Strain of Small Business Owners in Germany - Otto, Kathleen; Baluku, Martin Mabunda; Hünefeld, Lena; Kottwitz, Maria U. (Frontiers in Psychology, 2020)
Much research has been done on the economic effects of self-employment, environmental conditions for entrepreneurial success, as well as attributes if the person him-/herself fits to this career path. To successfully run a business, however, is contingent on the health of the entrepreneur. In particular, small business owners (being solo self-employed without personnel) face financial uncertainties, a high workload, long working hours, and are often unable to call in sick. This study aimed at exploring the working situation considering resources (e.g., autonomy), strain (e.g., dependency on contracts with clients) and health and career outcomes of small business owners. This study used a qualitative approach to comprehensively mirror the working situation. Participants who were 29 small business owners from Germany gave permission for recording expert interviews in which they reported, for example, on health complaints, recovery opportunities, obstacles and resources while running their businesses. The interviews emphasize the meaning of active actions and own responsibility for creating working conditions and enabling autonomy. Small business owners yet have to be able to use the autonomy. Besides personal preferences regarding the career path as being pulled into self-employment and not pushed by situational circumstances also marketability and flexibility played a role and explained health and career issues. Our findings underline that the social network is of utmost importance to small business owners and that social support – even or despite of being solo self-employed – is a key to sustaining health and satisfaction. As voluntariness played an essential role for selecting this specific career path those being pulled into self-employment as no other jobs are available should receive particular support through career counseling. One shortcoming of prior research is that the concrete working situation of small business owners and its impact on health and career has not adequately been taken into account. Based on work-related stress models we developed a frame model specific for the situation of small business owners which allows concrete hypotheses for further quantitative research.